Octopus ORAM: An Oblivious RAM with Communication and Server Storage Efficiency - Ma, Qiumao; Zhang, Wensheng (EAI Endorsed Transactions on Security and Safety, 2019)
Most of existing ORAM constructions have communication efficiency as the major optimization priority; the server storage efficiency, however, has not received much attention. Motivated by the observation that, the server storage efficiency is as important as communication efficiency when the storage capacity is very large and/or the outsourced data are not frequently accessed, we propose in this paper a new ORAM construction called Octopus ORAM. Through extensive security analysis and performance comparison, we demonstrate that, Octopus ORAM is secure; also, it significantly improves the server storage efficiency, achieves a comparable level of communication efficiency as state-of-the-art ORAM constructions, at the cost of increased client-side storage, and the increased client-side storage should be affordable to the clients who adopt local facilities such as cloud storage gateways.